Plasticity of collective behavior in a nomadic early spring folivore - Despland, Emma (Frontiers in Physiology, 2013)
Collective behaviour in the forest tent caterpillar (Malacosoma disstria) meets the thermal constraints of being an early spring folivore, but introduces others constraints in food choice. These are minimized by state-dependent, inter-individual and ontogenetic variations in responses to social cues. Forest tent caterpillars use pheromone trails and tactile communication among colony members to stay together during foraging. At the group level, these rules lead to cohesive synchronised collective nomadic foraging, in which the colony travels en masse between feeding and resting sites. This paper proposes that synchronized collective locomotion prevents individuals from becoming separated from the colony and hence permits them to reap the advantages of group living, notably collective basking to increase their body temperature above ambient and collective defense against natural enemies. However, this cohesive behaviour also implies conservative foraging, and colonies can become trapped on poor food sources. High fidelity to pheromone trails leads to strong amplification of an initial choice, such that colonies seldom abandon the first food source contacted, even if a better one is nearby. The risk of this trapping is modulated both by consistent inter-individual variations in exploratory behaviour and by inner state. Colonies consisting of active-phenotype or protein-deprived individuals that explore more off trails exhibit greater collective flexibility in foraging. An ontogenetic shift toward more independent movement occurs as caterpillars grow. This leads to colony break-up as the season advances. Selection pressures facing older caterpillars favour solitary living more than in the earlier instars. Caterpillars respond to this predictably changing environment by altering their behavioural rules as they grow.